Role of Advanced Manufacturing Technology, Human Capital and Employee Empowerment to Enhance Manufacturing Industry Supply Chain Performance - Tanawat Wisedsin; Kittisak Jermsittiparsert; Phitphisut Thitart; Wissawa Aunyawong (International Journal of Supply Chain Management, 2020)
Human resource and Technology are the important assets of the organization. For this reason, the purpose of the present study was to examine the impact of advanced Manufacturing technology, human capital and employee empowerment on supply chain performance, furthermore, the mediating role of organizational innovation is examined as well. The data is collected from the employees of manufacturing firms in Indonesia in the form of questionnaire. The response rate of the current study is 63.4 percent. For analysis, Partial least square (PLS) software is specifically used for the statistical analysis of data and presenting the results that are obtained for the model, since PLS is capable of flexibly generating, estimating as well as validating the complex models. The findings of the study support all the proposed hypothesis showing the importance of human capital and technology to bring innovation and improve the performance of supply chain. The findings of the present study are important for the practitioners of supply chain sector.